O processo de formação de conceitos nas crianças de 4 a 6 anos de idade - Tartari, Fernanda Maeli (2019)
This research was developed through the Stricto Sensu Postgraduate Program in Education - Masters level - area of concentration: Education, Culture research line, Educational Processes and Teacher Training, of the State University of the West of Paraná - UNIOESTE. It is part of the researches perfomed in the Study and Research Group of Teaching and Learning and Historical-Cultural Theory (GEPEAThc). The teaching of young children, especially in the period of transition from Kindergarten to Elementary Education, is substantial to the year´s sequence of schooling. During this period, children continue and consolidate the foundations of their development, which has been initiated since their entry into basic education. Therefore, our study has as it´s research theme the formation of concepts by children at the beginning of schooling. We aim to understand how concepts are formed in children from 4 to 6 years of age. For this study, we conducted a qualitative and bibliographical research based on the works of Historical-Cultural Theory, having as main references the texts and essays of L. S. Vygotsky, psychology and Soviet educators. Also, we use the contributions of contemporary researchers, who performed their investigations based and from the classical authors of this Theory. So, we started the text by presenting some researches made in Brazil, at Masters and Doctoral level, in the area of Education, which approach the self formation of the Human Kind from this theoretical reference. In the sequence, we tried to identify the historical context and emergence of the Historical-Cultural Theory, as well as its theoreticalmethodological foundations. From this perspective, we briefly discuss the process of human psychological development, specifically, the development of the child from 4 to 6 years of age. Next, we tried to understand the stages of concept formation through which children go (syncretic, complex, concepts) and the formation of mental action. In this process, it is important to emphasize the role of the teacher as the one responsible for teaching planning and pedagogical activity, in order to promote the bases of the formation of scientific concepts in children. In the sequence, we reflected on the relations between the formation of the pseudo-concepts and the potential concepts still in the pre-school age. We also analyzed psychic development through main activity and mental action. This way, we consider that the teaching process must approach the experiences of preschool children, where the understanding of phenomena is at the pseudoconcept stage. However, through the systematic organization of teaching strategies, we need to guide it to abstract the essential attributes and properties of the studied phenomena, in order to promote the internalization of this knowledge in the form of potential concepts. In this path, we understand that the organization of teaching with the objective of forming concepts can be developed by the formation of the stages of mental action. During the teaching activity, it is necessary to contemplate the plays, since they ate the guiding activity of the child with 4 to 6 years of age, being the one that governs the most relevant changes in the psychic processes in this period. We conclude that in this course of development, the teacher has a fundamental role, since it is responsible for the organization of systematized teaching in the school institution.